Canteen Food Waste Reduction Strategies Using the Life Cycle Assessment Method - Fajar Mochammad Ichwan; Atikha Sidhi Cahyana (Universitas Muhammadiyah Sidoarjo, 2022)
Food waste is a global issue which is currently the center of attention of the world community. Starting from developing countries to developed countries trying to solve the problem of food waste that occurs in the country. As is well known, the amount of food waste or food waste is increasing every day, both from industry and households or restaurants, in Sidoarjo alone can produce as much as 2,400 tons of waste per day with 116 TPSTs, which can only manage 600 tons of waste per day. well managed. Part of the waste consists of leftover food and vegetables from restaurant and industrial including wastefood waste ,from a company canteen. For large companies with thousands of employees, food scraps will definitely pile up every day. Therefore, this study aims to find a strategy to reduce food waste in the company canteen. In order to produce output that is in line with expectations, it must be used an appropriate method. The method used in this research is the LCA (Method life Cycle Assessment)which can help to solve problems, find the cause and effect of the main problem widely. LCA is a method used to analyze potential environmental impacts arising from an activity, by reducing the use of raw materials and transportation, implementing pollution control, reducing environmental emissions and utilizing waste. In this research, the result is Waste percentage is the percent of product loss caused in cooking, trimming, portioning or cleaning. With the normal limit of the waste percentage generated by a restaurant or canteen is 37-41%, PT. ECCO is still on the normal threshold with a percentage of 39%.